Understanding parental choices related to infant sleep practices in the United States using a mixed methods approach - Hannah Sahud; Rachel P. Berger; Megan Hamm; Emily Heineman; Flor Cameron; Julia Wasilewski; Ashley Griffin; Gysella B. Muniz (BMC Pediatrics)
Abstract Background This study aimed to gather information about parental practices, knowledge, and attitudes regarding infant sleep habits and environments, among families who practice non-recommended sleep practices. Methods We conducted one-on-one phone interviews with parents who had practiced non-recommended sleep methods with their infant and had or had not experienced an undesirable sleep event such as a fall. Interviews were recorded and coded with MAXQDA software. Intercoder reliability was assessed for consistency. Results Thirty-one parents consented, and 21 interviews were conducted. Parents were aware of current American Academy of Pediatrics (AAP) sleep recommendations for infants, knew about the sleep risks of non-recommended practices and had access to a recommended sleep environment. Parents reported developing modifications to the sleep environment which they perceived made their infant’s sleep safer. Many parents felt that they could not be honest with their primary care provider about utilizing a non-recommended sleep environment; many had not had a detailed conversation with their primary care provider about safe sleep. Conclusions Our data are consistent with previous studies which demonstrate that lack of access to a recommended sleep space or lack of knowledge about AAP sleep guidelines are not the primary reasons for practicing non-recommended sleep habits. Our data highlights the disconnect between the current AAP safe sleep recommendations and what parents feel is feasible to do on a daily basis. Evaluating the impact of a risk elimination strategy which is used in the US compared with a risk mitigation strategy which is used in other countries on parental practice and ability to communicate honestly with primary care providers is a future area of research.